Rosja w poszukiwaniu modelu reżimu politycznego – „poliarchia zachodnia” czy „azjatycka demokracja” - Potulski, Jakub (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
One of the fields of interest of modern political science involves the process of transformation of political systems, understood as the transition from nondemocratic to democratic systems. One of the countries undergoing such a political transformation is the Russian Federation, which in the nineteen-nineties faced the need to reject the model of the socio-political system of the Soviet Union, and to adjust to the emerging global civilization dominated by the models originating in West European countries. The paper emphasizes that, on account of the difficulties related to the process of political transformation, at the beginning of the new millennium West European models began to be supplanted by the models of Asian countries enjoying impressive economic growth while maintaining paternalist and authoritarian mechanisms of power. The author of the paper stresses that the political system of the modern Russian Federation is a particular mix of European and Asian models. Its functioning does not resemble the political regimes of polyarchy as much as those described as ‘Asian democracies’. The author indicates that given the present developmental stage of the Russian Federation, this models appears to be more practical and adequate in the political and cultural reality of modern Russia.